2022
DOI: 10.22541/au.166607827.72423871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age and gender differences of electrocardiographic basic values and abnormalities in general adult population; Tehran Cohort Study

Abstract: Introduction Although several studies are available regarding baseline Electrocardiographic (ECG) parameters, major and minor ECG abnormalities, there is a big controversy regarding their age and gender differences in literature, thus we aimed to investigate any possible age or gender ECG discrepancies in general adult population. Methods Data of 7630 adults aged ≥35 years from Tehran Cohort Study who were registered between March 2016 to March 2019 were collected. ECG basic values, major, and minor ECG abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…This study showed that minor and major ECG abnormalities increased with aging in women. In line with our research, In both genders, the odds of presenting major ECG abnormalities surge with a rise in age 27,28 . The etiology of the observed ECG variations between age groups are not completely identified.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that minor and major ECG abnormalities increased with aging in women. In line with our research, In both genders, the odds of presenting major ECG abnormalities surge with a rise in age 27,28 . The etiology of the observed ECG variations between age groups are not completely identified.…”
Section: Discussionsupporting
confidence: 91%
“…These ECG differences between age groups may be contributed to developmental, electrical, and structural conduction system alternations in the heart throughout life 29 . Moreover, differences in the atherosclerosis and other CVDs risks, comorbidities, medications, and lifestyle parameters can also affect ECG components at different ages 28,30 . www.nature.com/scientificreports/ HTN is one of the main risk factors for CVD.…”
Section: Discussionmentioning
confidence: 99%